Giving Children With Osteogenesis Imperfecta a Voice: Participatory Approach for the Development of the Interactive Assessment and Communication Tool Sisom OI - Siedlikowski, Maia; Rauch, Frank; Tsimicalis, Argerie (JMIR Publications, 2020)
BackgroundChildren with osteogenesis imperfecta (OI) experience acute and chronic symptoms that expose them to physical, mental, and social challenges. Empowering these children by involving them in their care can help them to cope with OI. Sisom is an interactive assessment and communication tool designed to help children aged 6-12 years with chronic illnesses express their symptoms. This tool has not yet been adapted to the unique needs of OI. ObjectiveThe aim of this study was to develop a Sisom OI paper prototype by seeking the perspectives of end users. MethodsA participatory approach was adopted to develop the prototype overseen by an expert panel of 9 clinicians at a university-affiliated pediatric hospital. Purposive sampling was used to recruit 12 children with OI who were aged 6-12 years. The study was carried out over the course of 3 feedback cycles. Data were deductively interpreted using content analysis techniques. ResultsOverall, 64% (57/89) of the Sisom symptoms were deemed relevant for inclusion in Sisom OI, with 42% (37/89) directly incorporated and 22% (20/89) incorporated with changes. In total, 114 symptoms were used to create the prototype, of which 57 were newly generated. The relevant symptoms addressed children's thoughts and feelings about hospitalization and their wishes for participation in their own care. The new symptoms addressed fractures, body image, and social isolation related to difficulties with accessibility and intimidation. ConclusionsOnce developed, Sisom OI will offer clinicians an innovative and child-centered approach to capture children's perspectives on their condition.